Lymph node metastasis is not associated with survival in patients with clinical stage T4 esophageal squamous cell carcinoma undergoing definitive radiotherapy or chemoradiotherapy - Zhu, Liqiong; Zhao, Zongxing; Liu, Ao; Wang, Xin; Geng, Xiaotao; Nie, Yu; Zhao, Fen; Li, Minghuan (Frontiers in Oncology, 2022)
Background: Clinical T4 stage esophageal tumors are difficult to be surgically resected, and definitive radiotherapy or chemoradiotherapy remains the main treatment. In this study, we investigated the ability of lymph node (LN) metastasis to predict prognosis in patients with clinical T4 esophageal squamous cell carcinoma (ESCC) undergoing treatment with definitive radiotherapy or chemoradiotherapy. Methods: We retrospectively reviewed data from 555 patients with ESCC treated with definitive radiotherapy or chemoradiotherapy in two medical centers from April 2010 to December 2017. Kaplan-Meier and Cox regression analyses were carried out to determine the relationship between LN metastasis and prognosis. The chi-square test was used to assess tumor recurrence patterns at different clinical T stages. Results: Three-year survival rates were 33.9% and 17.8% for patients with non-cT4 ESCC and cT4 ESCC, respectively. Overall survival (OS) and progression-free survival (PFS) were strongly associated with LN metastasis status in the entire cohort (all p < 0.001) and the non-cT4 subgroup (all p < 0.001) but not in the cT4 subgroup. Local recurrence rates were 61% in patients with cT4 ESCC and 39.2% in those with non-cT4 disease (p < 0.001). Multivariate analysis showed that clinical N stage (hazard ratio [HR], 1.534; 95% confidence interval [CI], 1.189–1.980; p = 0.001), LN size (≥2 cm; HR, 1.502; 95% CI, 1.060–2.129; p = 0.022), and abdominal LN involvement (HR, 1.462; 95% CI, 1.026–2.085; p = 0.036) independently predicted favorable survival in the entire cohort. Similarly, clinical N stage (HR, 1.599; 95% CI, 1.195–2.140; p = 0.002), LN size (HR, 1.737; 95% CI, 1.167–2.587, p = 0.007), and abdominal LN involvement (HR, 1.681; 95% CI, 1.126–2.512; p = 0.011) were independent predictors of favorable survival in the non-T4 subgroup. However, LN metastasis status failed to predict OS and PFS in patients with cT4 ESCC. Conclusions: Our data suggest that LN metastasis does not independently predict survival in patients with cT4 ESCC receiving definitive radiotherapy or chemoradiotherapy. Local recurrence is the main recurrence pattern in patients with cT4 esophageal tumors.